If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3cos(3x) + -1 = 0 Remove parenthesis around (3x) 3cos * 3x + -1 = 0 Reorder the terms for easier multiplication: 3 * 3cos * x + -1 = 0 Multiply 3 * 3 9cos * x + -1 = 0 Multiply cos * x 9cosx + -1 = 0 Reorder the terms: -1 + 9cosx = 0 Solving -1 + 9cosx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 9cosx = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 9cosx = 0 + 1 9cosx = 0 + 1 Combine like terms: 0 + 1 = 1 9cosx = 1 Divide each side by '9osx'. c = 0.1111111111o-1s-1x-1 Simplifying c = 0.1111111111o-1s-1x-1
| 6x^2-60x= | | 7.5w+25=-1 | | 2x+12+3x-18+3z+4y=360 | | 3x=10-7 | | 4y=487-13X | | 18n^2-192n+270= | | 2x-4=4x-14 | | -3-9a-4-5a=7 | | -7n^2+58n-16= | | 5cotx+4=9 | | 800=5x+11y | | 9p-21=-21+3p | | 2n^2-36n+160= | | 10000=n-9050 | | 5p-17=-11+8p | | 5y-7x=16 | | 4=r^68 | | n^2+19n-2000=0 | | -5(2t+8)=-90 | | 4(f-7)=-16 | | 7(3x+14)+12=-19 | | 18x-10=10x+70 | | g=-4*-4 | | 6x+7y-6=0 | | 3x-15=3-5x | | 5x+7=42forx | | 10(s-10)=-146 | | s+40=0 | | 1/7(-14s)= | | -2x=8-2x | | (3x)/3=(4-1)/3 | | 4+-3a+18a^2= |